2008
DOI: 10.1158/1078-0432.ccr-07-4102
|View full text |Cite
|
Sign up to set email alerts
|

KIT Mutations Induce Intracellular Retention and Activation of an Immature Form of the KIT Protein in Gastrointestinal Stromal Tumors

Abstract: Purpose: Gastrointestinal stromal tumors (GIST) are frequently associated with gain-of-function mutations of KIT, which can be inhibited by imatinib both in vitro and in vivo. The survival of patients with GIST, following imatinib therapy, has been correlated with the nature of mutations but not with KITexpression. Experimental Design: Subcellular localization, activation, and trafficking of the mature and the immature forms of KIT were investigated in GIST samples and in NIH3T3 cells infected with two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 44 publications
7
70
0
1
Order By: Relevance
“…2 A and B, the presence of WT KIT and the N505I mutant on the cell surface is higher than that of T417IΔ418-419 and Dup A502Y503 mutants. The presence of the cytoplasmic domain mutants V560D, D816V, and V560DY823D on the cell surface was very low, in accordance with previous reports (18,19). We also used fluorescence microscopy to visualize the cellular distribution of a green fluorescent protein (GFP) fused to WT or each oncogenic KIT mutant expressed in COS7 cells.…”
Section: Kit Cellular Distribution and Dynamic Properties Are Affectesupporting
confidence: 82%
See 2 more Smart Citations
“…2 A and B, the presence of WT KIT and the N505I mutant on the cell surface is higher than that of T417IΔ418-419 and Dup A502Y503 mutants. The presence of the cytoplasmic domain mutants V560D, D816V, and V560DY823D on the cell surface was very low, in accordance with previous reports (18,19). We also used fluorescence microscopy to visualize the cellular distribution of a green fluorescent protein (GFP) fused to WT or each oncogenic KIT mutant expressed in COS7 cells.…”
Section: Kit Cellular Distribution and Dynamic Properties Are Affectesupporting
confidence: 82%
“…We and others (18,19) have shown that glycosylated WT KIT migrates on SDS/PAGE as two distinct bands with apparent molecular masses of 145 kDa and 125 kDa ( Fig. 2 C and D).…”
Section: Kit Cellular Distribution and Dynamic Properties Are Affectementioning
confidence: 58%
See 1 more Smart Citation
“…Ainsi, nous avons observé que des formes mutées de KIT ont un devenir biochimique très différent. En effet, elles existent majoritairement à l'état immature (non ou peu glycosylées), sont principalement localisées dans le réticulum endoplasmique ou l'appareil de Golgi, mais sont peu exprimées à la surface cellulaire [30]. De plus, les formes immatures de KIT peuvent être phosphorylées et transmettre un signal d'activation cellulaire ( Figure 5).…”
Section: Biochimie Des Formes Mutées Et Sauvages De Kitunclassified
“…12 KIT mutations have been detected principally (66% to 71%) in gene portions encoding for the juxtamembrane region, most often exon 11, followed by the fifth extracellular immunoglobulin-like region encoded by exon 9 (13%), and less frequently in the tyrosine kinase domain 1 encoded by exon 13 (1% to 4%) and the phosphotransferase domain encoded by exon 17 (>1% to 4%).…”
mentioning
confidence: 99%